Executive function and self-regulated exergaming adherence among older adults - Anderson-Hanley, Cay; Arciero, Paul J.; Barcelos, Nicole; Nimon, Joseph; Rocha, Tracey; Thurin, Marisa; Maloney, Molly (Frontiers in Human Neuroscience, 2014)
The rise in dementia and the evidence of cognitive benefits of exercise for the older adult population together make salient the research into variables affecting cognitive benefit and exercise behavior. One promising avenue for increasing exercise participation has been the introduction of exergaming, a type of exercise that works in combination with virtual reality to enhance both the exercise experience and health outcomes. Past research has revealed that executive function (EF) was related to greater use of self-regulatory strategies, which in turn was related to greater adherence to exercise following an intervention (McAuley et al., 2011). Best et al. (2014) found improvement in EF related to adherence to exercise post- intervention. Anderson-Hanley et al. (2012) found that for older adults aerobic exergaming yielded greater cognitive benefit than traditional exercise alone; however, questions remain as to the possible impact of greater cognitive benefit and other factors on participants’ involvement in exercise following the end of an intervention. The current study presents follow-up data exploring the relationship between change in EF, self-regulation, and exercise adherence in the post-intervention (naturalistic) period. Herein, it was predicted that improvement in EF during an exercise intervention, would predict subsequent exercise with an exergame during the naturalistic window. Contrary to expectations, results suggest that those with EF decline during the intervention used the exergame more frequently. The results of this study contradict previous literature, but suggest an interesting relationship between change in executive function, self-regulation, and exercise behaviors when exergaming is employed, particularly with older adults with some cognitive decline. We hypothesize that other factors may be at work; perhaps expectation of cognitive benefit might act as a unique motivator or caregivers may be instrumental in adherence.